WandaVision : the complete series [videorecording (Blu-Ray)] - Schaeffer, Jac (Marvel Studios, 2023)
After the Infinity War, Wanda Maximoff and Vision are two super-powered beings living idealized suburban lives, who begin to suspect that everything is not as it seems.